Quasiconformal mappings and radii of normal systems of neighborhoods - Gol'berg, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish a new geometric criterion for plane homeomorphisms to belong to the class ofq-quasiconforrnal mappings.